Answer:
h = 7, k = 6
Explanation:
Solving 2 simultaneous equations
2h +
= 17 ← multiply through by 2 to clear the fraction
4h + k = 34 → (1)
3h +
= 23 ← multiply through by 3 to clear the fraction
9h + k = 69 → (2)
Subtract (1) from (2) term by term to eliminate k
(9h - 4h) + (k - k) = (69 - 34), that is
5h = 35 ( divide both sides by 5 )
h = 7
Substitute h = 7 in either of the 2 equations for corresponding value of k
Substituting h = 7 in (1)
4(7) + k = 34
28 + k = 34 ( subtract 28 from both sides )
k = 6